GLP-1 — The New Darling of Diabetes Treatment - Gater, Laura (MD Conference Express, 2006)
Glucagon-like peptide-1 (GLP-1) is an incretin hormone that regulates postprandial insulin secretion. The incretin effect is believed to be critical for maintenance of normal plasma glucose and glucose tolerance [Diab 1995]. Experiments using antagonists of the GLP-1 receptor show that GLP-1 is responsible for a substantial part of the insulin response to oral glucose [Diab 1995; Diab 1994]. This article discusses GLP-1 receptor agonists and DPP IV inhibitors.